Embryonic developmental arrest in the annual killifish Austrolebias charrua: A proteomic approach to diapause III. - Cora Chalar (Public Library of Science (PLoS), 2021)
Diapause is a reversible developmental arrest faced by many organisms in harsh environments. Annual killifish present this mechanism in three possible stages of development. Killifish are freshwater teleosts from Africa and America that live in ephemeral ponds, which dry up in the dry season. The juvenile and adult populations die, and the embryos remain buried in the bottom mud until the next rainy season. Thus, species survival is entirely embryo-dependent, and they are perhaps the most remarkable extremophile organisms among vertebrates. The aim of the present study was to gather information about embryonic diapauses with the use of a "shotgun" proteomics approach in diapause III and prehatching Austrolebias charrua embryos. Our results provide insight into the molecular mechanisms of diapause III. Data are available via ProteomeXchange with identifier PXD025196. We detected a diapause-dependent change in a large group of proteins involved in different functions, such as metabolic pathways and stress tolerance, as well as proteins related to DNA repair and epigenetic modifications. Furthermore, we observed a diapause-associated switch in cytoskeletal proteins. This first glance into global protein expression differences between prehatching and diapause III could provide clues regarding the induction/maintenance of this developmental arrest in A. charrua embryos. There appears to be no single mechanism underlying diapause and the present data expand our knowledge of the molecular basis of diapause regulation. This information will be useful for future comparative approaches among different diapauses in annual killifish and/or other organisms that experience developmental arrest.